Perbandingan Kadar Elektrolit Serum Pascaenterektomi Ekstensif 75 % pada Anjing yang Diterapi dengan Laktoferin - Setiawan, Boedi; -, Sudarminto; -, Hartiningsih (Jurnal Veteriner; Vol 11 No 2 (2010))
A severe and extensive intestine damages can occur in dogs suffering from volvulus , strangulation,intersuception and neoplasia. Extensive enterectomy is the most common medical treatment for dogssuffering from such disorder. A study was therefore conducted to compare the serum electrolyte level ofextensively enterectomyzed dogs after being treated with different level (0%, 0.05% and 0.5 mg/bodyweight) of lactoferin. As many as 9 dogs at 3-4 moth-old and with the body weights ranging from 4-5 kgwere used. After being enterectomized to the extent of 75% out of the total length of the intestine, the dogswere divided randomly into 3 groups (I, II and III) each of which consisted of 3 dogs. The three groups weretreated for 30 days respectively with 0.0 mg/body weight, 0.05mg/kg body weigth and 0.5mg/kg bodyweight of lactoferin. The electrolyte levels (Na, K and Cl ion) of dogs were determined at days 1, 15 and 30of during the treatment. The data collected from this study were analysed by Analysys of Variance (Anova)proceded by Duncan Multiple Range test (DMRT). The result showed that at days 15 and 30 of thetreatment, the electrolyte levels of the dogs with lactoferin (0.05 and 0.5 mg/body weight) were significantlyhigher than in dogs without lactoferin (0mg/bodyweight). The level of Na ion of dogs with 0,5, 0,05, dan 0mg/kg bw lactoferin were 143, 143,4, dan 141,7 mEq/L respectively at day 15 and 147, 150, dan 137,7mEq/L respectively at day 30. The levels of K ion for those dogs were 5,17, 4,97, dan 3,83 mEq/Lrespectively at day 15 and 30: 5,1, 5,13, 3,73 mEq/L respectively at day 30. Meanwhile, their Cl levelswere 113,7, 114,3, 104 mEq/L respectively at day 15 and 115,3, 117,3, dan 91,3 mEq/L respectively atday 30. Hasil penelitian ini menunjukkan bahwa memperian lactoferin memperbaiki kadar elektrolitserum anjing yang dienterektomi secara ekstensif. It was evidence that lactoferin treatment can improvedthe electrolyte profiles of extensively enterotomized dogs.